Wpływ kursu walutowego na wyniki działalności przedsiębiorstwa agrobiznesu - Dubicka, Danuta; Orłowska, Maria J.; Zdrenka, Ewa (Rate of Exchange Influence on Financial Results of Agribusiness Enterprise, 2005)
Analysed rates of exchange influence functioning and financial results for enterprises acting outside their countries. Research are done for agribusiness enterprise during 2000-2003.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 166-171